ANALISIS MANAJEMEN RISIKO PADA PROYEK PEMBANGUNAN BENDUNGAN (STUDI KASUS : BENDUNGAN TITAB DI BALI, BENDUNGAN JATIBARANG DI KABUPATEN SEMARANG DAN BENDUNGAN DIPONEGORO DI SEMARANG) - Helen Gianditha Wayangkau (Civil Infrastructure Engineering and Architectural Design, 2021)
ABSTRACTConstruction of dam project has complicated characteristics, as a result it has varios kinds of risks that influential the implementation. The larger scale of the project makes the risk of project potential more growing, so it needs a risk management in order to minimize the potential risk.In general to manage the risk management, stakeholders are often analysed it by using Risk Breakdown Structure method (RBS). However by using RBS is not sufficient because it just to get a risk category. It necessary the level of risk analysis by PROMETHEE method to find out priority major rangking on construction project.To support and improve the management of dam project development activity, it implemented risk assesment. As many as 31 variabels risk related to the project was successfuly identified. The survey through quistionares have sent to 1 expert who representative of the owner on ministry of public works, directorat of water resources and 1 expert in private companies who have experience in each of dam, also taken 1 people around the located who was affected by the impact directly. This research used quantitative descriptive method.The result of this research were obtained that the risk of social environment is the highest potential risk which is almost same in every project.The risk of social environment is alocated to the government because the review of land acquistion depended with the authority and the policy of the authorities. In addition it obtained a low and high a risk that happened in research field refers to the impact not about the probability. If the probability is low and the impact is high then the risk goes highest. Preferably in a high probability and its impact is low then the risk is insignificant.Keywords : Management Risk, PROMETHEE, Risk, Risk Breakdown Structure.